Defragmenting Student’s Thinking Structures in Solving Mathematical Problems on PISA Model - M. Gunawan Supiarmo ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2021)
Problem solving is defined as a series of activities that allow students to find solutions to problems. Students' thinking processes occur when processing data or information to solve problems. One way to help students maximize the thinking skills is to make their experience when solving problems with PISA model. But in reality, Students made many mistakes and have difficulty understanding the problem, making a settlement plan, lack knowledge of the prerequisite material, and have not been able to describe the reasons in detail regarding the solutions found. One of the possible solutions to improve and complete the structure of students' thinking in solving mathematical problems on the PISA model HOTS questions is defragmenting. This study aims to describe the changes of students' thinkingstructure in solving mathematical problems through defragmenting. This type of research is descriptive research with a qualitative approach. The research data consisted of students' answers, the results of thinking aloud, and the results of semi-structured interviews. The results showed that students experienced assimilation at the stage of understanding the problem, while at the stage of formulating strategies, implementing plans, and re-examining students' thinking processes, they experienced accommodation. This is because students need defragmenting to connect mathematical concepts to solve problems, correct errors, and complete incomplete problem solving steps.